PENALARAN BERBASIS KASUS UNTUK DIAGNOSA PENYAKIT ANAK DENGAN PENGOBATAN HERBAL - , TURSINA, ST ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Case-based reasoning for diagnose of disease in children by using herbal medicine is to diagnose the disease suffered by children which associated with respiratory and lung diseases. The reasons for research on childhood diseases related to respiratory tract and lungs is due to respiratory disease and lung disease is most often experienced by children. Therefore it takes an intelligent system that resembles the expert in the form of case-based reasoning. The medication suggested by the expert on this system is the herbal medicine. Case-based reasoning is reasoning that aims to solve new problems by adapting solutions found in previous cases that have a similar problem with a new case. The main source of knowledge on a case-based reasoning system is based on cases that already exist or which have been stored in the base case. The cases in support of this study were obtained from medical records of childhood disease (lung and breathing) from the RS. Panti Rapih Jogjakarta. The processes of case-based reasoning through four stages of the retrieve, reuse, revise, and retain. Calculation of similarity of cases is done by the Simple Matching Coefficient (SMC) and Jaccard Coefficient. Threshold value for similarity in this study was 0.95. If the similarity value below from the specified threshold value of the case will be updated to only be done by experts. Testing the system with the SMC method and Jaccard to the 100 new cases have a value of 89% accuracy. The similarity values generated by the Jaccard coefficient method is smaller than the SMC.